Violencia de pareja y alexitimia en adultos. - Ati Tacuri, Johana Gabriela (2024)
Partner violence is a mechanism of domination that encompasses a series of actions that cause physical, sexual, and psychological harm, exerting control over the partner. Significant psychological sequelae affect the victims, leaving deep traces that are manifested both physically and emotionally. Within this context, alexithymia, which ischaracterized by having difficulties in identifying and expressing emotions, adds a layer of complexity to understanding and coping with the emotional consequences of intimate partner violence. This research aimed to analyze the relationship between intimate partner violence and alexithymia through a documentary review and systematization of the information. The research corresponds to a bibliographic review of cross-sectional design at a descriptive level. The population consisted of 214 documents published from 2014 to 2024 in English, Spanish, French, and Persian. The sample was non-probabilistic by convenience; 48 articles were collected through scientific databases such as Pubmed, Scient Direct, ProQuest, and Scielo. Bibliographic review and documentary quality review were used as techniques; the bibliographic review form and the CRF-QS matrix were used as instruments. Results: Various forms of violence were identified, such as physical, sexual, patrimonial, and economic violence, with psychological violence emerging as predominant in relationships. In addition, high and borderline levels of alexithymia were described in both victims and perpetrators of violence. A significantly positive correlation was found between intimate partner violence and alexithymia. Conclusion: The results of this study conclusively support the existence of a direct relationship between alexithymia and the experience of violence in intimate partner relationships.